Effect of Different Container Colors on Behaviour and the Quality of Comet Fish (Carassius auratus) - Desi Gita Harini; Mulyadi Mulyadi; Usman M Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             Thisresearch was conducted on 24 October until 02 December 2018 at Aquaculture Technology Laboratory of Fisheries and Marine, University Riau, Pekanbaru. The purpose of this experiment was to investigate the effect of container for behaviour and colour quality of comet fish (Carassius  auratus). The research method use in this study was an experimental method and completely randomized design with five treatments and three replication. The treatments in this study were (P0) white container, (P1) black container, (P2) blue container, (P3) yellow container, (P4)combination container. Colour The result show that behaviour in containers that are bright fish are more active swimming in groups compared to dark colors fish. The result shownP3 (yellow container) that is 8,20 and P2 (blue container) is 5,67.The absolute best weight growth in P2(blue container) 2,71 g, absolute long growth in treatment in P3(yellow container) 2,24 cm and the best survival treatments have P0, P2 dan P3 especially 100%. Keywords:Behaviour, color quality,comet fish.